(untitled) (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This article analyzes the attention paid to history in the Republic of Uzbekistan during the years of independence, the enrichment of research areas in the field of history, and the issues of training historians.